Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 1 - Section 1.6 - Properties of Integral Exponents - Exercise Set: 52

Answer

$\dfrac{a^{-3}b^8}{c^{-2}} =\dfrac{b^8c^2}{a^3}$

Work Step by Step

RECALL: The negative-exponent rule of exponents states that: $a^{-m} =\dfrac{1}{a^m}$ and $\dfrac{1}{a^{-m}} = a^m$, where $a \ne 0$. Use the negative-exponent rule to find: $\dfrac{a^{-3}b^8}{c^{-2}} =\dfrac{\frac{b^8}{a^3}}{\frac{1}{c^2}}=\dfrac{b^8}{a^3} \cdot \dfrac{c^2}{1}=\dfrac{b^8c^2}{a^3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.